Analisis Pengaruh sikap dan norma subyektif terhadap niat beli kembali : Studi Empiris pada produk susu bubuk berlabel halal - Astuti, Widhy Tri (Akutansi Bisnis & Manajemen ( ABM ), 2006)
This study is an i lementation of Theog of Reasoned Action, that Attitude and Subjective Norm as independence variables and &purchase Intention as the dependen variable. The object of this study is PT Nestle Milk Powder as the sample of halal label of food product. Moesiem consumer Yogyakart were a, ,en as the sample of this study The results show that Attitude and SOjective Norm wen,positively and significaiitly influence the Repurchase Intention on halal label ty',food product